2019
DOI: 10.1155/2019/9589306
|View full text |Cite
|
Sign up to set email alerts
|

Mofette Vegetation as an Indicator for Geogenic CO2 Emission: A Case Study on the Banks of the Laacher See Volcano, Vulkaneifel, Germany

Abstract: A geogenic CO2 emitting site (mofette U1) at the banks of the Laacher See, Eifel Mountains, was chosen to study the relationship between heavy postvolcanic soil degassing and vegetation during spring season. To test any interrelation between soil CO2 degassing and vegetation, soil chemism (pH, water content, conductivity, and humus content) and vegetation studies (number of species, plant-soil coverage) were performed. Geogenic soil degassing patterns of carbon dioxide and oxygen were clearly inhomogeneous, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In Campania, Haworth et al (2010) studied the population of Agrostis canina growing close to natural springs of Mefite d'Ansanto (AV) emitting CO 2 , SO 2 , and H 2 S (Paoletti et al 2005); the authors showed that individuals living in these so harsh conditions possess resistance to toxic gases and are adapted to grow at elevated CO 2 levels, even if this resistance is not associated with a reduction in stomatal index. In the German mofettes, Pfanz et al (2019) point out that the number of species and the vegetation cover decrease with increasing CO 2 concentration and only a few marsh species such as Carex acutiformis and Phragmites australis grow closer to the emission areas.…”
Section: Mofettes and Mud Volcanoesmentioning
confidence: 99%
“…In Campania, Haworth et al (2010) studied the population of Agrostis canina growing close to natural springs of Mefite d'Ansanto (AV) emitting CO 2 , SO 2 , and H 2 S (Paoletti et al 2005); the authors showed that individuals living in these so harsh conditions possess resistance to toxic gases and are adapted to grow at elevated CO 2 levels, even if this resistance is not associated with a reduction in stomatal index. In the German mofettes, Pfanz et al (2019) point out that the number of species and the vegetation cover decrease with increasing CO 2 concentration and only a few marsh species such as Carex acutiformis and Phragmites australis grow closer to the emission areas.…”
Section: Mofettes and Mud Volcanoesmentioning
confidence: 99%